Preparation method and application of graphene / LDH hybrid composite material
By mixing waste incineration fly ash and aluminum ash with acidic fermentation waste liquid, disposing by mechanical chemical ball milling, graphene/LDH hybrid composite materials are prepared, and the problems of waste incineration fly ash and aluminum ash are solved, and the effects of resource utilization and heavy metal adsorption are achieved.
Patent Information
- Application Number
- CN202411981655.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to effectively treat and utilize waste incineration fly ash and aluminum ash, resulting in environmental pollution and waste of resources.
Graphene/LDH hybrid composite material is prepared by mixing waste incineration fly ash and aluminum ash with the acidic fermentation waste liquid generated by the biochemical process and disposing of it by mechanical chemical ball milling.
The resource utilization of waste incineration fly ash and aluminum ash has been achieved, the amount of industrial inorganic acids and disposal costs have been reduced, and the adsorption performance and economic value of heavy metals have been improved.
Smart Images

Figure CN119608111A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and specifically relates to a preparation method and application of a graphene / LDH hybrid composite material. Background Art
[0002] A large amount of waste generated in the process of life and urban development, such as fly ash from garbage incineration, aluminum ash, slag, slag, fly ash, electroplating wastewater, etc., mostly contain toxic substances. If not disposed of, it will cause pollution to the environment. For example, fly ash from garbage incineration contains highly toxic organic compounds and heavy metals, which will cause serious harm to the human body; small particles of aluminum ash dust can easily enter the air to pollute the atmospheric environment, and the seepage of water-soluble salt ions, heavy metals, etc. may cause land salinization. Therefore, the harmless resource disposal of solid waste will also become one of the important environmental protection issues. On the other hand, these wastes contain a large amount of valuable elements such as Ca, Si, and Al. Using them to prepare layered double hydroxides (LDHs) and apply them can effectively promote the resource utilization of waste and reduce the production cost of LDHs.
[0003] LDHs is an anionic clay material, which consists of a main layer, interlayer anions and water molecules. The most typical synthesis method is a co-precipitation method combined with a hydrothermal method. At present, there are corresponding studies in the application directions of catalysts, adsorbents, flame retardants, corrosion inhibitors, etc. LDHs prepared from waste have similar properties to LDHs synthesized from pure chemical reagents. However, since the composition of waste is often more complex, the composition of synthesized LDHs will also be more complex. For example, the main layer may contain a variety of metal elements, and there may be a variety of different anions between the layers, which may affect its properties and performance, and increase the difficulty of exploring the application mechanism. However, complex components may enhance its performance. Compared with ordinary LDHs, LDHs prepared from waste have higher economic and environmental value.
[0004] Therefore, it is very necessary to explore an efficient and low-cost method for preparing GLDH using waste incineration fly ash and aluminum ash slag to achieve the coordinated treatment of hazardous waste and industrial solid waste. Summary of the invention
[0005] In order to solve at least one of the above problems, the present invention provides a preparation method and application of a graphene / LDH hybrid composite material.
[0006] In order to achieve the above object, the present invention adopts the following technical means: A first aspect of the present invention provides a method for preparing a graphene / LDH hybrid composite material, comprising the following steps: S1. Add waste incineration fly ash and aluminum ash to fermentation waste liquid respectively, mix and extract them fully, take the filtrate after filtering, and collect the fly ash residue for later use; S2: The obtained fly ash filtrate and aluminum ash filtrate are treated according to the divalent metal cation Ca 2+ and trivalent metal cation Al 3 + The molar ratio of the mixture is greater than 1.5:1, and the pH is adjusted to 10-12, and a mixed suspension is obtained after sufficient stirring; S3: transferring the mixed suspension to a ball mill, adding graphene oxide, steel slag, and fly ash residue obtained in step S1, and subjecting the mixed suspension to mechanochemical ball milling treatment; S4: centrifuging, filtering, washing and drying the mixed solution in S3 to obtain a graphene / LDH hybrid composite material.
[0007] In a specific embodiment of the present invention, after the fly ash filtrate and the aluminum ash filtrate are mixed, the pH is adjusted to 11.
[0008] In some embodiments of the present invention, the fermentation waste liquid is an acidic waste liquid with a pH of 1 to 5 produced by a biochemical process.
[0009] In some embodiments of the present invention, the fermentation waste liquid can also be replaced by an inorganic acid solution, and the inorganic acid is acetic acid or hydrochloric acid.
[0010] In some specific embodiments, the waste incineration fly ash is added to a 0.4-0.5M acetic acid solution at a rotation speed of 600-700 rpm, and the acid washing is stirred for 20-24 hours; the aluminum ash is added to a 0.2-0.3M hydrochloric acid solution at a rotation speed of 400-500 rpm, and the acid washing is stirred for 10-12 hours; the obtained mixed solutions are respectively filtered through a 0.45μm filter membrane to obtain the filtrate.
[0011] In some embodiments of the present invention, in step S1, the liquid-to-solid ratio is (5-10):1, and the extraction time is 12-24 hours.
[0012] In some embodiments of the present invention, the mass ratio of the graphene oxide, the steel slag, and the fly ash residue obtained in step S1 is (0.01-0.1): 1:1; the graphene oxide and the divalent metal cation Ca in the mixed suspension 2+ The molar ratio is (0.01-0.1):1.
[0013] In some embodiments of the present invention, the mechanochemical ball milling treatment conditions in step S3 are: ball-to-material ratio (8-10):1.
[0014] In some embodiments of the present invention, the mechanochemical ball milling treatment has a ball milling time of 2-6 hours and a ball milling speed of 300-600 rpm.
[0015] In some embodiments of the present invention, in step S4, the washing step is two deionized water washes and one ethanol wash.
[0016] In some embodiments of the present invention, in step S4, the drying condition is 50-110°C.
[0017] The present invention also provides a graphene / LDH hybrid composite material prepared by the method described in the first aspect.
[0018] The present invention also provides an application of the graphene / LDH hybrid composite material prepared by the method described in the first aspect in the adsorption of heavy metals in wastewater.
[0019] In some embodiments of the present invention, the present invention is applied to the adsorption of heavy metal Cd in wastewater.
[0020] In some embodiments of the present invention, the present invention is applied to the adsorption of heavy metal Cu in wastewater.
[0021] The present invention also provides an application of the graphene / LDH hybrid composite material prepared by the method described in the first aspect in improving soil, wherein the soil is contaminated by heavy metals Cd and / or Cu.
[0022] In the application of soil improvement, the graphene / LDH hybrid composite material is mixed with contaminated soil.
[0023] Beneficial Effects of the Invention Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention utilizes waste fermentation liquid from biological or chemical processes to extract effective components in fly ash and aluminum ash, replacing the use of industrial hydrochloric acid, sulfuric acid, acetic acid, etc., while reducing the purchase cost and disposal cost caused by the use of industrial inorganic acid, and can also synergistically treat waste fermentation liquid from biological or chemical processes, reducing the additional disposal cost of waste fermentation liquid. The present invention utilizes fly ash from garbage incineration, aluminum ash, graphene, and steel slag to synthesize GLDH, and through the synergistic disposal and high-value utilization of multiple hazardous wastes, replaces waste landfill treatment, fully utilizes effective components, reduces environmental pollution, and improves economic value.
[0024] In general, LDHs are prepared by ball milling using fly ash from garbage incineration, aluminum ash and acidic fermentation waste liquid produced by biochemical process. On the one hand, fly ash from garbage incineration, aluminum ash, acidic waste liquid and steel slag produced by biochemical process are utilized as resources, reducing the costs of fly ash solidification landfill, fly ash aluminum ash steel slag treatment, and acidic waste liquid treatment. On the other hand, the prepared graphene / LDH hybrid composite material is used for heavy metal adsorption, reducing the consumption of pure reagents and generating huge economic benefits. The method of the present invention can not only stabilize fly ash, but also has simple process, easy preparation, low equipment requirements, universality, and can be widely promoted and used.
[0025] (2) In the preparation process of the graphene / LDH hybrid composite material (GLDH), the present invention uses a mechanochemical method to directly synthesize a composite GLDH based on graphene oxide (GO) and montmorillonite, thereby eliminating the step-by-step preparation process of GLDH, making the overall reaction process more efficient and reducing economic costs.
[0026] (3) In the present invention, montmorillonite is produced from steel slag and fly ash through ball milling. At the same time, under the action of graphene oxide, the prepared GLDH has a large specific surface area and can expose more active sites. It can be widely used in the adsorption of heavy metals in wastewater and soil improvement. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD diagram of the graphene / LDH hybrid composite material obtained in Example 3 of the present invention is shown; Figure 2 The heavy metal adsorption performance comparison of the composite materials prepared under different pH conditions in Examples 1 to 6 is shown; Figure 3 The heavy metal adsorption performance comparison of the composite materials prepared under different pH conditions in Examples 1 to 3 is shown; Figure 4 The different Ca values of Examples 1 and 7-10 are shown. 2+ 、Al 3+ Comparison of heavy metal adsorption performance of composite materials prepared under different conditions; Figure 5 The heavy metal adsorption performance of the composite materials prepared under different graphene addition conditions in Example 1 and Examples 15-20 is compared. DETAILED DESCRIPTION
[0028] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.
[0030] The technical solution of the present application is further described in detail below in conjunction with specific implementation methods.
[0031] A method for preparing a graphene / LDH hybrid composite material comprises the following steps: S1. Add waste incineration fly ash and aluminum ash to the acidic fermentation waste liquid with a pH of 1-5 produced by the biochemical process, respectively, with a liquid-to-solid ratio of (5-10):1, fully mix and extract for 12-24 hours, filter and collect the filtrate, and collect the fly ash residue for later use; S2: The obtained fly ash filtrate and aluminum ash filtrate are treated according to the divalent metal cation Ca 2+ and trivalent metal cation Al 3 + The molar ratio of the mixture is greater than 1.5:1, and the pH is adjusted to 10-12, and a mixed suspension is obtained after sufficient stirring; S3: Transfer the mixed suspension to a ball mill, add graphene oxide, steel slag, and the fly ash residue obtained in step S1, and perform mechanochemical ball milling treatment, wherein the mass ratio of graphene oxide, steel slag, and the fly ash residue obtained in step S1 is (0.01-0.1): 1: 1; the graphene oxide and the divalent metal cation Ca in the mixed suspension are 2+ The molar ratio is (0.01-0.1):1; in the ball milling process, the ball-to-material ratio is (8-10):1, the ball milling time is 2-6h, and the ball milling speed is 300-600rpm. S4: centrifuging, filtering and washing the mixed solution in S3, wherein the washing steps include two deionized water washings and one ethanol washing; after washing, drying at 50-110° C. is performed to obtain a graphene / LDH hybrid composite material.
[0032] In the above scheme, the fermentation waste liquid can also be replaced by an inorganic acid solution, and the inorganic acid is acetic acid or hydrochloric acid.
[0033] In some specific embodiments, the waste incineration fly ash is added to a 0.4-0.5M acetic acid solution at a rotation speed of 600-700 rpm, and the acid washing is stirred for 20-24 hours; the aluminum ash is added to a 0.2-0.3M hydrochloric acid solution at a rotation speed of 400-500 rpm, and the acid washing is stirred for 10-12 hours; the obtained mixed solutions are respectively filtered through a 0.45μm filter membrane to obtain the filtrate.
[0034] The present invention also relates to a graphene / LDH hybrid composite material prepared by the method and its application in sewage heavy metal adsorption and soil improvement.
[0035] Example 1 A method for preparing a graphene / LDH hybrid composite material comprises the following steps: S1. Add waste incineration fly ash and aluminum ash to the acidic fermentation waste liquid with pH 4 produced by the biochemical process, with a liquid-to-solid ratio of 8:1, respectively, mix and extract for 22 hours, take the filtrate after filtering, and collect the fly ash residue for later use; S2: The obtained fly ash filtrate and aluminum ash filtrate are treated according to the divalent metal cation Ca 2+ and trivalent metal cation Al 3 + The mixture is mixed in a molar ratio of 2:1 and the pH value is adjusted to 11, and a mixed suspension is obtained after sufficient stirring; S3: The mixed suspension is transferred to a ball mill, and graphene oxide, steel slag and fly ash residue obtained in step S1 are added in a mass ratio of 0.02:1:1, and subjected to mechanochemical ball milling treatment, wherein the graphene oxide and the divalent metal cation Ca in the mixed suspension are 2+ The molar ratio of the ball to the material was 0.02:1; in the ball milling treatment, the ball to material ratio was 10:1, the ball milling time was 6h, and the ball milling speed was 600rpm. S4: The mixed solution in S3 was centrifuged at a speed of 5500 rpm, filtered, washed twice with deionized water and once with ethanol, and dried at 80° C. after washing to obtain a graphene / LDH hybrid composite material.
[0036] Example 2 The other operation steps are the same as those in Example 1, except that: in step S2, 2M NaOH solution is added to adjust the pH to 10.
[0037] Example 3 The other operation steps are the same as those in Example 1, except that: in step S2, 2M NaOH solution is added to adjust the pH to 12.
[0038] Example 4 The other operation steps are the same as those in Example 1, except that: in step S2, 2M NaOH solution is added to adjust the pH to 12.5.
[0039] Example 5 The other operation steps are the same as those in Example 1, except that: in step S2, 2M NaOH solution is added to adjust the pH to 13.
[0040] Example 6 The other operation steps are the same as those in Example 1, except that: in step S2, 2M NaOH solution is added to adjust the pH to 13.5.
[0041] Example 7 The other operation steps are the same as those in Example 1, except that: in step S2, the divalent metal cation Ca 2+ and trivalent metal cation Al 3+ The molar ratio is 3:1.
[0042] Example 8 The other operation steps are the same as those in Example 1, except that: in step S2, the divalent metal cation Ca 2+ and trivalent metal cation Al 3+ The molar ratio is 4:1.
[0043] Example 9 The other operation steps are the same as those in Example 1, except that: in step S2, the divalent metal cation Ca 2+ and trivalent metal cation Al 3+ The molar ratio is 5:1.
[0044] Example 10 The other operation steps are the same as those in Example 1, except that: in step S2, the divalent metal cation Ca 2+ and trivalent metal cation Al 3+ The molar ratio is 6:1.
[0045] Embodiment 11 The other operation steps are the same as those in Example 1, except that the ball milling speed in step S3 is set to 300 rpm.
[0046] Example 12 The other operation steps are the same as those in Example 1, except that the ball milling speed in step S3 is set to 400 rpm.
[0047] Embodiment 13 The other operation steps are the same as those in Example 1, except that the ball milling time in step S3 is set to 2 h.
[0048] Embodiment 14 The other operation steps are the same as those in Example 1, except that the ball milling time in step S3 is set to 4 h.
[0049] Embodiment 15 The other operation steps are the same as those in Example 1, except that steel slag and fly ash residue obtained in step S1 are added in a mass ratio of 1:1 in step S3.
[0050] Example 16 The other operation steps are the same as those in Example 1, except that: in step S3, graphene oxide, steel slag and fly ash residue obtained in step S1 are added in a mass ratio of 0.01:1:1.
[0051] Embodiment 17 The other operation steps are the same as those in Example 1, except that: in step S3, graphene oxide, steel slag and fly ash residue obtained in step S1 are added in a mass ratio of 0.015:1:1.
[0052] Embodiment 18 The other operation steps are the same as those in Example 1, except that: in step S3, graphene oxide, steel slag and the fly ash residue obtained in step S1 are added in a mass ratio of 0.3:1:1.
[0053] Embodiment 19 The other operation steps are the same as those in Example 1, except that: in step S3, graphene oxide, steel slag and the fly ash residue obtained in step S1 are added in a mass ratio of 0.5:1:1.
[0054] Embodiment 20 The other operation steps are the same as those in Example 1, except that: in step S3, graphene oxide, steel slag and the fly ash residue obtained in step S1 are added in a mass ratio of 1:1:1.
[0055] (1) The composite material prepared in Example 1 was tested for its main crystalline phase composition by X-ray diffraction (XRD). The XRD results are as follows: Figure 1 shown.
[0056] As can be seen from the figure, there are relatively sharp peaks at 10.5°, 11.3°, 22.6°, 23.4°, 31.0°, 38.8°, etc., which are typical characteristic peaks of LDHs.
[0057] (2) The adsorption materials prepared in Examples 1 to 20 above were subjected to adsorption tests: 0.05 g of the GLDH material prepared above was mixed with 100 ml of simulated liquid, the initial concentration of cadmium nitrate and copper nitrate in the simulated liquid was 500 mg / L, stirred at 200 rpm for 6 h, centrifuged at 7000 rpm for 5 min to obtain supernatant and separation slurry, the supernatant was filtered through a 0.22 μm filter to obtain the filtrate, and the concentration of heavy metal ions in the liquid phase before and after adsorption was determined by ICP-OES. The test results are shown in Table 1. Figures 2 to 5 shown.
[0058] Table 1 Adsorption performance of adsorbent materials obtained from Examples 1 to 20
[0059] The results show that: Figure 2 and 3 As shown, Examples 1 to 6 show that the pH of the mixture of the fly ash filtrate and the aluminum ash filtrate has an important influence on the adsorption performance of the final product, and the pH value = 11 is the optimal pH. When it exceeds 12, the adsorption performance of the product decreases significantly.
[0060] like Figure 4 As shown, Examples 1, 7 to 10 show that as the fly ash filtrate and the aluminum ash filtrate have Ca 2+ and Al 3+ With the increase of the proportion, the synthesis efficiency of the prepared GLDH is further improved, and the adsorption capacity is gradually improved. This method can improve the efficiency of the coordinated treatment of fly ash and aluminum ash, and the product also has good application prospects in the future.
[0061] Example 1, Example 11 and Example 12 show that as the ball milling time increases, the synthesis efficiency of the prepared GLDH is further improved and the adsorption capacity is gradually increased.
[0062] Example 1, Example 13 and Example 14 show that as the ball milling speed increases, the synthesis efficiency of the prepared GLDH is further improved and the adsorption capacity is gradually increased.
[0063] like Figure 5 As shown, Example 1, Example 15 to Example 20 show that as the amount of graphene oxide added increases, the adsorption capacity of the prepared GLDH also gradually increases, but when the amount added exceeds 0.5g / L, the adsorption capacity growth rate gradually decreases. When the amount of graphene oxide added is greater than 0.01g / L, the adsorption capacity of the prepared material for Cd reaches more than 734mg / g, and the adsorption capacity for Cu also reaches more than 428mg / g. Considering the cost of adding graphene oxide, the amount of graphene oxide added is not easy to be too high, and the preferred addition of graphene is 0.01-0.02g / L.
[0064] LDHs are prepared by ball milling using the acidic fermentation waste liquid produced by the coordinated biochemical process of waste incineration fly ash and aluminum ash. On the one hand, the waste incineration fly ash, aluminum ash, and acidic waste liquid produced by biochemical industry are utilized as resources, reducing the costs related to fly ash solidification landfill, aluminum ash treatment, steel slag treatment, and acidic waste liquid treatment. On the other hand, the prepared graphene / LDH hybrid composite material is used for heavy metal adsorption, reducing the consumption of pure reagents and generating huge economic benefits. The method of the present invention can not only achieve stabilization treatment of fly ash, but also has a simple process, is easy to prepare, has low equipment requirements, has universality, and can be widely promoted and used.
[0065] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.
Claims
1. A method for preparing a graphene / LDH hybrid composite material, characterized in that: The steps include: S1. Add waste incineration fly ash and aluminum ash to fermentation waste liquid respectively, mix and extract them fully, take the filtrate after filtering, and collect the fly ash residue for later use; S2: The obtained fly ash filtrate and aluminum ash filtrate are treated according to the divalent metal cation Ca 2+ and trivalent metal cation Al 3+ The molar ratio of the mixture is greater than 1.5:1, and the pH is adjusted to 10-12, and a mixed suspension is obtained after sufficient stirring; S3: transferring the mixed suspension to a ball mill, adding graphene oxide, steel slag, and fly ash residue obtained in step S1, and subjecting the mixed suspension to mechanochemical ball milling treatment; S4: centrifuging, filtering, washing and drying the mixed solution in S3 to obtain a graphene / LDH hybrid composite material.
2. The method according to claim 1, characterized in that: The fermentation waste liquid is an acidic waste liquid with a pH of 1-5 produced in a biochemical process.
3. The method according to claim 1, characterized in that: The fermentation waste liquid can also be replaced by an inorganic acid solution, wherein the inorganic acid is acetic acid or hydrochloric acid.
4. The method according to claim 1, characterized in that: In the step S1, the liquid-to-solid ratio is (5-10):1, and the extraction time is 12-24 hours.
5. The method according to claim 1, characterized in that: The mass ratio of the graphene oxide, steel slag, and fly ash residue obtained in step S1 is (0.01-0.1): 1: 1; the graphene oxide and the divalent metal cation Ca in the mixed suspension 2+ The molar ratio is (0.01-0.1):
1.
6. The method according to claim 1, characterized in that: The mechanochemical ball milling treatment conditions in step S3 are: ball-to-material ratio (8-10):
1.
7. The method according to claim 6, characterized in that: The ball milling time of the mechanochemical ball milling treatment is 2-6 hours, and the ball milling speed is 300-600 rpm.
8. The method according to claim 1, characterized in that: In step S4, the washing steps include two deionized water washes and one ethanol wash.
9. The method according to claim 1, characterized in that: In step S4, the drying condition is 50-110°C.
10. A graphene / LDHs hybrid composite material prepared by the method according to claims 1-9.
Citation Information
Patent Citations
Hydrotalcite and preparation method thereof
CN109437291A
Strong adsorption type graphene-based composite material used for sewage treatment
CN110918051A
Force-responsive polymer foam particle and preparation method thereof
CN111171364A
Heavy metal contaminated soil remediation agent based on graphene oxide and application thereof
CN115044379A
Preparation method of layered double-metal hydroxide based on waste incineration fly ash
CN116903015A